Limitations on the Utilization of Glycolate by Chlamydomonas reinhardtii - Spencer, Kenneth G. (1981)
Growth and shorter term incorporation measurements with both wild type Chlamydomonas reinhardtii and a mutant (F-60, lacking phosphori-bulokinase activity) indicate that the rate of glycolate utilization is always relatively low. Growth support with external glycolate is restricted to cells with full photosynthetic capacity. A high concentration of glycolate is required for optimal growth support and incorporation of [(14)C]glycolate. Glycolate incorporation is low at pH 3.8 even with the relatively free permeability. The F-60 mutant can take up only small quantities of glycolate in spite of photosynthetic electron transport and photophosphorylation competencies. This requirement for photosynthetic carbon metabolism indicates a significant difference in the glycolate pathway of this alga. No growth condition significantly increases glycolate incorporation rates. There is no evidence that one of the primary enzymes, glycolate dehydrogenase, is limiting utilization; measurements of glycolate uptake and excretion do not always correlate with its activity. Since the maximal utilization rate of glycolate is low, control of glycolate formation is important in preventing the loss of this fixed carbon from the algal cell.